Kompetensi Intervensi Fonetik Artikulasi bagi Anak Penyandang Down Syndrome - Hasan, Laili Mas Ulliyah; Nurharini, Firdausi; Salma, Kunti Nadiyah (Absorbent Mind: Journal of Psychology and Child Development, 2021)
The purpose of this study is to prove and measure the effectiveness and obtain results from research activities using a simple intervention on Muhammad Syauqi who has an IQ of 30-40. This study uses qualitative research with observation methods, namely observing in the field accompanied by analysis and distribution methods, namely listening, recording, changing, replacing. Descriptive analysis method is used to present information and data. Descriptive analysis method is used to present information and data. Data collection techniques were obtained through observation, interviews, and documentation. The results of Muhammad Syauqi's research stated that articulation phonetic intervention experienced an increase in pronunciation which was originally only able to pronounce A, U, O, D, G, H, M, P, Q, T, W, Y, Z to be able to pronounce B, C, E. , F, I, J, K, L, N, R, S, F, W, except X. Common obstacles that occurred during the research process were due to the subject's tongue being tired of pronouncing letters words and experiencing dizziness several times accompanied by the physical characteristics become cross-eyed eyes.